2002
DOI: 10.1161/hc0402.102619
|View full text |Cite
|
Sign up to set email alerts
|

The AT 1 -Type Angiotensin Receptor in Oxidative Stress and Atherogenesis

Abstract: D espite intense investigation in the last decade, many questions concerning the etiology of atherosclerosis remain unanswered. Hypercholesterolemia and hypertension are clearly risk factors for the development of vascular lesions, although the precise molecular steps between elevated lipid or blood pressure levels and the development of atherosclerotic lesions are not completely defined. 1,2 Hypertension is frequently associated with additional risk factors such as hypercholesterolemia, estrogen deficiency, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
90
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(93 citation statements)
references
References 73 publications
(44 reference statements)
1
90
0
2
Order By: Relevance
“…Because atherosclerosis can be a diffuse process, it is possible that hypertension is a manifestation of a diffuse atherosclerotic process in large conduit arteries, as well as smaller resistance vessels. 4 Nickenig and Harrison 7,8 have linked lipids and hypertension via a mechanism of angiotensin I overexpression. Lipid abnormalities and insulin resistance have been associated with sympathetic hyperfunction, 25 which may play a role in the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Because atherosclerosis can be a diffuse process, it is possible that hypertension is a manifestation of a diffuse atherosclerotic process in large conduit arteries, as well as smaller resistance vessels. 4 Nickenig and Harrison 7,8 have linked lipids and hypertension via a mechanism of angiotensin I overexpression. Lipid abnormalities and insulin resistance have been associated with sympathetic hyperfunction, 25 which may play a role in the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…AT1 is constitutively expressed in placental VSMCs as shown in the Western blot data. AT1 plays important roles in angiogenic, inflammatory and oxidative stress responses in the placental vasculature [30][31][32][33]. A recent study by Herse et al showed that AT1 receptor mRNA expression was 10-fold higher in the placenta than in the decidua tissues in both normal and preeclamptic pregnancies, but no difference was noticed for AT1 mRNA expression between normal and preeclamptic placental tissues [34].…”
Section: Discussionmentioning
confidence: 99%
“…A key response of endothelial cells and inflammatory cells to Ang II is increased production of ROS and the consequent imbalance between ROS and NO. 47,52 This pro-oxidative effect of Ang II results from its engagement to the high-affinity angiotensin II type 1 (AT 1 ) receptor, which leads to the activation of NAD(P)H. 53 The proinflammatory AT 1 receptor is found on endothelial cells and circulating blood cells, including neutrophils, monocytes, T lymphocytes, and platelets. AT 1 receptor antagonists block the oxidative stress induced in these cells by Ang II.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…54,55 The possibility that Ang II and AT 1 receptors are involved in eliciting the oxidative stress and leukocyte-endothelial cell adhesion of hypercholesterolemia is supported by studies of both large and microscopic blood vessels. 52,65 Furthermore, surrogate markers for endothelial activation and inflammation (eg, sVCAM-1) indicate that RAS-directed drugs might exert some of their beneficial effects by controlling the inflammatory response that accompanies CVD.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%